Tantalum-doped hafnium oxide ferroelectric film and preparation method thereof
The preparation of tantalum doped hafnium dioxide ferroelectric films by chemical solution method solved the problems of poor response, poor performance and high cost of ferroelectric films, and achieved efficient and low-cost ferroelectric film preparation.
Patent Information
- Application Number
- CN202510114917.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-06
AI Technical Summary
In the prior art, there are problems of poor response, poor ferroelectric performance and high cost.
A tantalum doped hafnium dioxide ferroelectric film was prepared by chemical solution method. By mixing hafnium salt, tantalum salt, organic solvent and catalyst, an Hf1-xTaxO2 precursor solution was formed, and then dripped, dried, and pre-annealed and annealed to obtain a ferroelectric film with good ferroelectric properties.
The good response and performance of ferroelectric films are achieved, and the preparation cost is reduced, avoiding dependence on large equipment and vacuum environments.
Smart Images

Figure CN119947130A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ferroelectric thin films, and in particular to a tantalum-doped hafnium dioxide ferroelectric thin film and a preparation method thereof. Background Art
[0002] Ferroelectric memory, as a new type of non-volatile memory, has been gradually applied to communications, aerospace, mobile terminals and other fields due to its advantages such as low power consumption, high erase and write times, non-volatility, and fast read and write speed. The incompatibility of traditional ferroelectric materials with existing CMOS processes and the limited ability to shrink the size are the problems that need to be solved urgently from the proposal to the industrialization of ferroelectric memory. In contrast, HfO2-based ferroelectric films are compatible with the CMOS process system and have good ferroelectric properties even at extremely thin thicknesses, and have great potential for application in actual production in the future.
[0003] At present, the methods used to prepare HfO2-based ferroelectric films include atomic layer deposition, pulsed laser deposition, magnetron sputtering and chemical solution method. Using different methods to prepare HfO2-based ferroelectric films will lead to differences in film performance. Literature has confirmed that the use of pulsed laser deposition and magnetron sputtering to prepare tantalum-doped hafnium dioxide films will produce orthorhombic phases and have ferroelectricity, but there is a phenomenon that the leakage current is very large and masks the transient current peak, resulting in poor ferroelectric response. In addition, the above two preparation methods rely on high-cost equipment, have complex operating steps, and have strict requirements on the film preparation process. The chemical solution method has the advantages of simple process and easy control of stoichiometric ratio; at the same time, its preparation process does not involve large equipment and high vacuum environment, and has low requirements on the overall hardware conditions and cost of the experiment.
[0004] Therefore, it is very important to provide a tantalum-doped hafnium dioxide thin film with good ferroelectric response, good ferroelectric performance and low cost. Summary of the invention
[0005] The object of the present invention is to provide a tantalum-doped hafnium dioxide ferroelectric film and a preparation method thereof, so as to solve the technical problems of poor response, poor ferroelectric performance and high cost of the ferroelectric film in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a tantalum-doped hafnium dioxide ferroelectric film, wherein the molecular formula of the tantalum-doped hafnium dioxide ferroelectric film is Hf 1-x Ta x O2, where 0.05≤x≤0.2.
[0008] The present invention also provides a method for preparing the tantalum-doped hafnium dioxide ferroelectric thin film, comprising the following steps:
[0009] 1) Mix hafnium salt, tantalum salt, organic solvent and catalyst to obtain Hf 1-x Ta x O2 precursor solution;
[0010] 2) Hf 1-x Ta x The O2 precursor solution is dropped onto the substrate surface and then spin-coated and dried to obtain the initial Hf 1-x Ta x O2 ferroelectric thin film samples;
[0011] 3) Set the initial Hf 1-x Ta x The O2 ferroelectric thin film samples were subjected to pre-annealing and annealing treatments in sequence to obtain Hf 1- x Ta x O2 ferroelectric thin film.
[0012] Furthermore, in step 1), the hafnium salt includes one or more of hafnium acetylacetonate, hafnium n-butoxide, hafnium tetranitrate and hafnium isopropoxide;
[0013] The tantalum salt includes tantalum alkoxide;
[0014] The organic solvent includes one or more of anhydrous ethanol, ethylene glycol, ethylene glycol methyl ether and toluene;
[0015] The catalyst includes one or more of acetic acid, nitric acid and citric acid.
[0016] Furthermore, the Hf 1-x Ta x The concentration of metal cations in the O2 precursor solution is 0.05-0.2 mol / L;
[0017] The mass ratio of the hafnium salt to the tantalum salt is 0.3-0.5:0.03-0.05;
[0018] The volume ratio of the organic solvent to the catalyst is 1:2 to 3:1.
[0019] Furthermore, the mixing temperature is 40 to 60° C., and the mixing time is 10 to 30 minutes.
[0020] Furthermore, in the step 2), the substrate includes one of germanium, platinum, gallium nitride, gallium arsenide, p-type single crystal silicon wafer, p-type multi-crystalline silicon wafer, n-type single crystal silicon wafer, and n-type multi-crystalline silicon wafer.
[0021] Furthermore, in the step 2), the spin coating is sequentially low-speed spin coating and high-speed spin coating, the speed of the low-speed spin coating is 400-600 rpm, and the time of the low-speed spin coating is 15-25 s;
[0022] The speed of the high-speed spin coating is 2500-4000 rpm, and the time of the high-speed spin coating is 25-35 s.
[0023] Furthermore, in the step 3), the temperature of the pre-annealing treatment is 300-450° C., and the time of the pre-annealing treatment is 1-5 minutes.
[0024] Furthermore, in the step 3), the annealing temperature is 500-800° C., and the annealing time is 1-5 min.
[0025] Furthermore, in the step 2), the drying is carried out in an air atmosphere, the drying temperature is 170 to 210° C., and the drying time is 3 to 5 minutes;
[0026] In the step 3), the atmospheres of the pre-annealing treatment and the annealing treatment are independently one or more of air atmosphere, oxygen atmosphere and nitrogen atmosphere.
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention adopts a chemical solution method to prepare a tantalum-doped hafnium dioxide ferroelectric thin film with good ferroelectric properties, which expands the types of doping elements for preparing hafnium dioxide thin films using a chemical solution method;
[0029] (2) The film prepared by the preparation method adopted by the present invention has better ferroelectric response, and the film has good density, low roughness, and no cracks. It does not require a vacuum environment and large equipment, and the overall process cost is low;
[0030] (3) The preparation method adopted by the present invention is easy to carry out element doping, can accurately control the stoichiometric ratio of the doping elements, will not cause waste of resources, can also prepare thin films on a large area, and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The preparation flow chart of the tantalum-doped hafnium dioxide ferroelectric thin film prepared in Example 1;
[0032] Figure 2 X-ray diffraction patterns of tantalum-doped hafnium dioxide ferroelectric thin films prepared in Example 1 and Comparative Example 1;
[0033] Figure 3 Surface morphology of tantalum-doped hafnium dioxide ferroelectric thin films prepared in Example 1 and Comparative Example 1;
[0034] Figure 4 The hysteresis loop and transient current-electric field curve of the tantalum-doped hafnium dioxide ferroelectric thin film prepared in Comparative Example 1;
[0035] Figure 5The hysteresis loop and transient current-electric field curve of the tantalum-doped hafnium dioxide ferroelectric thin film prepared in Example 1;
[0036] Figure 6 The durability curve diagram of the tantalum-doped hafnium dioxide ferroelectric thin film prepared in Example 1 and Comparative Example 1;
[0037] Figure 7 The hysteresis loop and transient current-electric field curve of the tantalum-doped hafnium dioxide ferroelectric thin film prepared in Example 2;
[0038] Figure 8 The hysteresis loop and transient current-electric field curve of the tantalum-doped hafnium dioxide ferroelectric thin film prepared in Example 3 are shown. DETAILED DESCRIPTION
[0039] The present invention provides a tantalum-doped hafnium dioxide ferroelectric film, wherein the molecular formula of the tantalum-doped hafnium dioxide ferroelectric film is Hf 1-x Ta x O2, wherein 0.05≤x≤0.2, preferably 0.12≤x≤0.18, further preferably 0.14≤x≤0.16, and even more preferably 0.15.
[0040] The present invention also provides a method for preparing the tantalum-doped hafnium dioxide ferroelectric thin film, comprising the following steps:
[0041] 1) Mix hafnium salt, tantalum salt, organic solvent and catalyst to obtain Hf 1-x Ta x O2 precursor solution;
[0042] 2) Hf 1-x Ta x The O2 precursor solution is dropped onto the substrate surface and then spin-coated and dried to obtain the initial Hf 1-x Ta x O2 ferroelectric thin film samples;
[0043] 3) Set the initial Hf 1-x Ta x The O2 ferroelectric thin film samples were subjected to pre-annealing and annealing treatments in sequence to obtain Hf 1- x Ta x O2 ferroelectric thin film.
[0044] In the present invention, in the step 1), the hafnium salt comprises one or more of hafnium acetylacetonate, hafnium n-butoxide, hafnium tetranitrate and hafnium isopropoxide, preferably one or more of hafnium acetylacetonate, hafnium tetranitrate and hafnium isopropoxide, and more preferably hafnium acetylacetonate and / or hafnium tetranitrate;
[0045] The tantalum salt comprises tantalum alkoxide, preferably tantalum ethoxide;
[0046] The organic solvent comprises one or more of anhydrous ethanol, ethylene glycol, ethylene glycol methyl ether and toluene, preferably one or more of anhydrous ethanol, ethylene glycol and toluene, more preferably anhydrous ethanol and / or ethylene glycol;
[0047] The catalyst comprises one or more of acetic acid, nitric acid and citric acid, preferably acetic acid and / or citric acid, and more preferably acetic acid.
[0048] In the present invention, the Hf 1-x Ta x The metal cation concentration in the O2 precursor solution is 0.05 to 0.2 mol / L, preferably 0.08 to 0.18 mol / L, and more preferably 0.12 to 0.13 mol / L;
[0049] The mass ratio of the hafnium salt to the tantalum salt is 0.3-0.5:0.03-0.05, preferably 0.35-0.45:0.035-0.048, and more preferably 0.4-0.42:0.04-0.045;
[0050] The volume ratio of the organic solvent to the catalyst is 1:2 to 3:1, preferably 1:2 to 2:1, and more preferably 2:1.
[0051] In the present invention, the mixing temperature is 40-60° C., preferably 45-55° C., and more preferably 50° C.; the mixing time is 10-30 min, preferably 15-25 min, and more preferably 20 min.
[0052] In the present invention, the mixing further includes stirring and standing, the stirring temperature is 16-32° C., preferably 18-30° C.; the stirring time is 4-6 hours, preferably 5 hours; and the standing time is 12-72 hours, preferably 36 hours.
[0053] In the present invention, in the step 2), the substrate comprises one of germanium, platinum, gallium nitride, gallium arsenide, p-type single crystal silicon wafer, p-type polycrystalline silicon wafer, n-type single crystal silicon wafer, and n-type polycrystalline silicon wafer, preferably one of germanium, platinum, gallium nitride, gallium arsenide, p-type single crystal silicon wafer, n-type single crystal silicon wafer, and n-type polycrystalline silicon wafer, and further preferably one of germanium, platinum, gallium nitride, gallium arsenide, p-type single crystal silicon wafer, and n-type single crystal silicon wafer.
[0054] In the present invention, Hf 1-x Ta x Before the O2 precursor solution is dripped onto the substrate, the substrate is cleaned and then dried. The drying temperature is 15-35°C, preferably 26°C; the drying time is 4-6 minutes, preferably 6 minutes; and the drying is carried out in an air atmosphere.
[0055] In the present invention, in the step 2), the spin coating is sequentially low-speed spin coating and high-speed spin coating, the speed of the low-speed spin coating is 400-600 rpm, preferably 450-550 rpm, and more preferably 500 rpm; the time of the low-speed spin coating is 15-25 s, preferably 15-20 s, and more preferably 15-17 s;
[0056] The speed of the high-speed spin coating is 2500-4000 rpm, preferably 2700-3600 rpm, and more preferably 2900-3100 rpm; the time of the high-speed spin coating is 25-35 s, preferably 27-32 s, and more preferably 30 s.
[0057] In the present invention, the spin coating and drying steps are repeated 2 to 6 times, preferably 4 to 5 times, and more preferably 4 times.
[0058] In the present invention, in step 2), drying is carried out in an air atmosphere, the drying temperature is 170-210° C., preferably 180-200° C., more preferably 180-190° C.; the drying time is 3-5 min, preferably 4 min.
[0059] In the present invention, in step 3), the temperature of the pre-annealing treatment is 300-450°C, preferably 370-430°C, and more preferably 400°C; the time of the pre-annealing treatment is 1-5 min, preferably 2-4 min, and more preferably 3 min.
[0060] In the present invention, in step 3), the annealing temperature is 500-800°C, preferably 550-700°C, and more preferably 600°C; the annealing time is 1-5 min, preferably 2-4 min, and more preferably 3 min.
[0061] In the present invention, in step 3), the atmospheres of the pre-annealing treatment and the annealing treatment are independently one or more of air atmosphere, oxygen atmosphere and nitrogen atmosphere, preferably air atmosphere and / or oxygen atmosphere, and more preferably air atmosphere.
[0062] In the present invention, after the annealing treatment, the obtained Hf 1-x Ta x The O2 ferroelectric thin film is cooled at a temperature of 30 to 50°C, preferably 35 to 45°C, and more preferably 40°C.
[0063] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0064] Example 1
[0065] 0.0366 g of tantalum ethoxide and 4 mL of anhydrous ethanol were mixed and stirred at 27 ° C for 20 min, then 0.3023 g of hafnium acetylacetonate was added and stirred again at 27 ° C for 20 min, then 2 mL of acetic acid was added and stirred at 50 ° C for 20 min, and finally stirred at 27 ° C for 5 h. After the stirring was completed, it was allowed to stand for 36 h to obtain Hf 0.85 Ta 0.15 O2 precursor solution;
[0066] Hf 1-x Ta x The O2 precursor solution was dropped onto the surface of an n-type silicon wafer substrate (crystal orientation (111)) with a size of 7 mm × 7 mm. The solution was first accelerated to 500 rpm for 15 s at a low speed, then accelerated to 3000 rpm for 30 s at a high speed. The temperature of the spin coater was then set to 180 °C. The Hf 0.85 Ta 0.15 The O2 film was dried for 4 min and the above steps were repeated 4 times until the initial Hf 0.85 Ta 0.15 O2 ferroelectric thin film samples;
[0067] In the rapid annealing furnace program, the pre-annealing temperature was set to 400°C, the pre-annealing time was set to 3 min, the annealing temperature was set to 600°C, the annealing time was set to 3 min, and then the initial Hf 0.85 Ta 0.15 The O2 ferroelectric thin film sample is placed in the chamber of a rapid annealing furnace, and then the annealing is started in the program, which will cause the Hf 1-x Ta x The O2 ferroelectric film was subjected to pre-annealing and annealing treatments in sequence, and after the annealing was completed, it was cooled to 40°C to obtain Hf 0.85 Ta 0.15 O2 ferroelectric thin film.
[0068] Example 2
[0069] Compared with Example 1, the difference is that the doping concentration of tantalum in Example 2 is 16 mol%, and the substrate is a p-type silicon wafer substrate. 0.84 Ta 0.16 O2 ferroelectric thin film;
[0070] Example 3
[0071] Compared with Example 1, the difference is that the concentration of tantalum in Example 3 is 20 mol%, and Hf 0.80 Ta 0.20 O2 ferroelectric thin film.
[0072] Comparative Example 1
[0073] Compared with Example 1, the difference is that no tantalum ethoxide is added in Comparative Example 1, and other conditions remain unchanged to obtain a hafnium dioxide ferroelectric thin film HfO2.
[0074] The ferroelectric thin films prepared in Example 1 and Comparative Example 1 were tested. The test results are as follows: Figures 2 to 6 The ferroelectric films prepared in Example 2 and Example 3 were tested, and the test results are shown in Figures 7-8 shown.
[0075] It can be seen from the above embodiments that the present invention provides a tantalum-doped hafnium dioxide ferroelectric thin film and a preparation method thereof. Figure 2 The X-ray diffraction patterns of the tantalum-doped hafnium dioxide ferroelectric thin films prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 2 It can be seen that an obvious diffraction peak is observed near 31.6° in the undoped HfO2 ferroelectric film, which corresponds to the monoclinic (111) crystal plane, indicating that the phase composition in the film is mainly paraelectric monoclinic phase. 0.85 Ta 0.15 The diffraction peak of the high symmetry phase corresponding to the O2 ferroelectric film at around 30.4° is more significant. This diffraction peak corresponds to the tetragonal (011) / orthorhombic (111) crystal plane, which means that there are ferroelectric orthorhombic phase and antiferroelectric tetragonal phase in the film at this time. Therefore, Hf 0.85 Ta 0.15 The proportion of ferroelectric phase in O2 ferroelectric film is significantly higher than that in undoped HfO2 ferroelectric film, which will lead to enhanced ferroelectricity of the film. Figure 3 The surface morphology of the tantalum-doped hafnium dioxide ferroelectric thin film prepared in Example 1 and Comparative Example 1 is shown in FIG. Figure 3 It can be seen that the surface roughness RMS of the undoped HfO2 ferroelectric film is 0.236nm. 0.85 Ta 0.15 The surface roughness RMS of the O2 ferroelectric film is 0.066 nm, so the obtained film has good density, low roughness and no cracks. A small ion sputtering instrument is used to deposit Pt electrodes on the hafnium oxide-based ferroelectric films of Example 1 and Comparative Example 1, respectively, to obtain Pt / Hf 1-x Ta x The hysteresis loop and transient current-electric field curve of the O2 / Si structure capacitor were measured using a ferroelectric analyzer. Figure 4 The hysteresis loop and transient current-electric field curve of the tantalum-doped hafnium dioxide ferroelectric thin film prepared in Comparative Example 1; Figure 5 The hysteresis loop and transient current-electric field curve of the tantalum-doped hafnium dioxide ferroelectric film prepared in Example 1 are shown in FIG. Figures 4-5It can be seen that compared with the undoped HfO2 ferroelectric film, at the same film thickness and temperature, Hf 0.85 Ta 0.15 A transient current peak appears in the O2 ferroelectric film, and the residual polarization intensity is 14.6μC / cm 2 , which is higher than the remnant polarization intensity of undoped hafnium oxide ferroelectric film (4.54μC / cm 2 ), namely Hf 0.85 Ta 0.15 O2 ferroelectric thin film has better ferroelectric properties. Figure 6 The durability curves of the tantalum-doped hafnium dioxide ferroelectric thin films prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 6 It can be seen that tantalum-doped hafnium oxide ferroelectric thin film Hf 0.85 Ta 0.15 O2 has good durability. 9 After the cycle, the residual polarization intensity of the film did not decrease significantly and could continue to work. Figure 7 The hysteresis loop and transient current-electric field curve of the tantalum-doped hafnium dioxide ferroelectric film prepared in Example 2 are shown in FIG. Figure 7 It can be seen that Hf with a tantalum doping concentration of 16 mol% is prepared on a p-type Si substrate. 0.84 Ta 0.16 O2 ferroelectric film, transient current peak appears, and the residual polarization intensity is 9.3μC / cm 2 . Figure 8 The hysteresis loop and transient current-electric field curve of the tantalum-doped hafnium dioxide ferroelectric film prepared in Example 3 are shown in FIG. Figure 8 It can be seen that the Hf with a tantalum doping concentration of 20 mol% is prepared on an n-type Si substrate. 0.80 Ta 0.20 O2 ferroelectric film, a weak transient current peak appears, and the residual polarization intensity is 11.7μC / cm 2 .
[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A tantalum-doped hafnium dioxide ferroelectric thin film, characterized in that: The molecular formula of the tantalum-doped hafnium dioxide ferroelectric film is Hf 1-x Ta x O2, where 0.05≤x≤0.
2.
2. A method for preparing the tantalum-doped hafnium dioxide ferroelectric thin film according to claim 1, characterized in that: The following steps are involved: 1) Mix hafnium salt, tantalum salt, organic solvent and catalyst to obtain Hf 1-x Ta x O2 precursor solution; 2) Hf 1-x Ta x The O2 precursor solution is dropped onto the substrate surface and then spin-coated and dried to obtain the initial Hf 1-x Ta x O2 ferroelectric thin film samples; 3) Initial Hf 1-x Ta x The O2 ferroelectric thin film samples were subjected to pre-annealing and annealing treatments in sequence to obtain Hf 1-x Ta x O2 ferroelectric thin film.
3. The method for preparing a tantalum-doped hafnium dioxide ferroelectric thin film according to claim 2, characterized in that: In the step 1), the hafnium salt includes one or more of hafnium acetylacetonate, hafnium n-butoxide, hafnium tetranitrate and hafnium isopropoxide; The tantalum salt includes tantalum alkoxide; The organic solvent includes one or more of anhydrous ethanol, ethylene glycol, ethylene glycol methyl ether and toluene; The catalyst includes one or more of acetic acid, nitric acid and citric acid.
4. The method for preparing a tantalum-doped hafnium dioxide ferroelectric thin film according to claim 2 or 3, characterized in that: The Hf 1-x Ta x The concentration of metal cations in the O2 precursor solution is 0.05-0.2 mol / L; The mass ratio of the hafnium salt to the tantalum salt is 0.3-0.5:0.03-0.05; The volume ratio of the organic solvent to the catalyst is 1:2 to 3:
1.
5. The method for preparing a tantalum-doped hafnium dioxide ferroelectric thin film according to claim 4, characterized in that: The mixing temperature is 40-60° C., and the mixing time is 10-30 min.
6. The method for preparing the tantalum-doped hafnium dioxide ferroelectric thin film according to claim 2, 3 or 5, characterized in that: In the step 2), the substrate includes one of germanium, platinum, gallium nitride, gallium arsenide, p-type single crystal silicon wafer, p-type multi-crystalline silicon wafer, n-type single crystal silicon wafer, and n-type multi-crystalline silicon wafer.
7. The method for preparing a tantalum-doped hafnium dioxide ferroelectric thin film according to claim 6, characterized in that: In the step 2), the spin coating is sequentially low-speed spin coating and high-speed spin coating, the speed of the low-speed spin coating is 400-600 rpm, and the time of the low-speed spin coating is 15-25 s; The speed of the high-speed spin coating is 2500-4000 rpm, and the time of the high-speed spin coating is 25-35 s.
8. The method for preparing a tantalum-doped hafnium dioxide ferroelectric thin film according to claim 7, characterized in that: In the step 3), the pre-annealing temperature is 300-450° C., and the pre-annealing time is 1-5 minutes.
9. The method for preparing a tantalum-doped hafnium dioxide ferroelectric thin film according to claim 7 or 8, characterized in that: In the step 3), the annealing temperature is 500-800° C., and the annealing time is 1-5 min.
10. The method for preparing a tantalum-doped hafnium dioxide ferroelectric thin film according to claim 9, characterized in that: In the step 2), drying is carried out in an air atmosphere at a drying temperature of 170 to 210° C. and a drying time of 3 to 5 minutes; In the step 3), the atmospheres of the pre-annealing treatment and the annealing treatment are independently one or more of air atmosphere, oxygen atmosphere and nitrogen atmosphere.